Implementation of Terrorism Prevention Policy: A Case Study of FKPT of West Java Province and Its Impact on Intolerance Levels - Isya Marjani, Gustiana; Heni Herlina, Euis (International Journal of Nusantara Islam, 2024)
This research endeavors to comprehensively investigate three pivotal dimensions pertaining to the governmental policy implementation aimed at mitigating terrorism in the province of West Java. The methodology adopted for this research employs a mixed-methods approach that amalgamates a thorough literature review with rigorous field research, underpinned by an analytical descriptive framework. Furthermore, this study employs a multifaceted analytical lens, drawing from political, theological, and anthropological perspectives to comprehensively analyze and interpret the collected data. The research findings underscore a pervasive atmosphere of intolerance in West Java, accompanied by a heightened susceptibility to radical ideologies, extremist actions, and terrorism-related radicalism. These findings shed light on the intricate cultural nuances that shape the identity of West Java residents. The empirical investigation conducted across six distinct regencies and cities (namely, Sukabumi Regency, Sukabumi City, Cianjur Regency, Kuningan Regency, Indramayu Regency, and Cirebon City) within West Java, which serve as the focal points of this research, consistently reveal a glaring absence of specialized counterterrorism policies within the region. In essence, this lacuna underscores a notable deficit in the implementation of counterterrorism strategies. Instead, the predominant policy landscape in each of the aforementioned regencies and cities is characterized by a convergence with the overarching principles of the Homeland Defense and National Insight programs. These programs, conceived as flagship initiatives under the purview of the provincial Kesbangpol (National Unity and Political Affairs Agency), are similarly embedded within the Kesbangpol structures at the regional level. Consequently, within the context of this research, the Homeland Defense and National Insight policies emerge as policy instruments that are categorically associated with counterterrorism efforts in West Java.